Multiple Anthropogenic Pressures Lead to Seed Dispersal Collapse of the Southernmost Palm Jubaea chilensis - Cordero, Sebastián; Gálvez, Francisca; Fontúrbel, Francisco E. (Frontiers in Ecology and Evolution, 2021)
Seed dispersal is a critical process for plant reproduction and regeneration. Successful recruitment depends on pre- and post-dispersal processes that complete a seed's journey until becoming a new plant. However, anthropogenic stressors may disrupt the seed dispersal process at some stages, collapsing plant regeneration and hampering its long-term persistence. The Chilean palm tree Jubaea chilensis is the southernmost and the only non-tropical palm species, which currently relies on the scatter-hoarding rodent Octodon degus for seed dispersal. We assessed seed fate by measuring predation and dispersal rates through experimental fieldwork in the Palmar de Ocoa site (located within La Campana National Park) and the Palmar El Salto. We also used previous reports on seed harvest and seedling herbivory to depict the whole J. chilensis seed dispersal process and assess the relative importance of different anthropogenic pressures. We asked the following questions: (1) What is the effect of human harvesting on J. chilensis recruitment? (2) Do native and exotic rodents predate J. chilensis seeds in the same way? and (3) Does post-dispersal herbivory matter? We found that J. chilensis fruits are harvested for human consumption, reducing pre-dispersal available seeds by removing about 23 tons per season. Then, post-dispersal seeds at the Ocoa palm grove are heavily predated by exotic (Rattus rattus) and native (Octodon spp.) rodents; only 8.7% of the seeds are effectively dispersed by Octodon degus. At Palmar El Salto, 100% of the seeds were predated by Rattus rattus, precluding further analysis. Finally, 70% of the seedlings were consumed by exotic herbivores (mainly rabbits), resulting in a success rate of 1.81%. Only 7.9% of the surviving seedlings become infantile plants (four yr-old). Our assessment suggests that J. chilensis has ageing populations with very few young individuals in disturbed sites to replace the old ones. For those reasons, we suggest increasing its conservation category to critically endangered as land-use change is rapidly fragmenting and shrinking the extant J. chilensis populations. We urge to take urgent actions to protect this relict palm, which otherwise may go extinct in the next decades.